Do nematode and macrofauna assemblages provide similar ecological assessment information? - Patrício, Joana (2012)
Do nematode and macrofauna assemblages provide similar ecological assessment information? To answer this question, in the summer of 2006, subtidal soft-bottom assemblages were sampled and environmental parameters were measured at seven stations covering the entire salinity gradient of the Mondego estuary. Principal components analysis (PCA) was performed on the environmental parameters, thus establishing different estuarine stretches. The ecological status of each community was determined by applying the Maturity Index and the Index of Trophic Diversity to the nematode data and the Benthic Assessment Tool to the macrofaunal data. Overall, the results indicated that the answer to the initial question is not straightforward. The fact that nematode and macrofauna have provided different responses regarding environmental status may be partially explained by local differentiation in microhabitat conditions, given by distinct sampling locations within each estuarine stretch and by different response-to-stress times of each benthic community. Therefore, our study suggests that both assemblages should be used in marine pollution monitoring programs.